2014
DOI: 10.1098/rstb.2012.0472
|View full text |Cite
|
Sign up to set email alerts
|

Relative timing: from behaviour to neurons

Abstract: Processing of temporal information is critical to behaviour. Here, we review the phenomenology and mechanism of relative timing , ordinal comparisons between the timing of occurrence of events. Relative timing can be an implicit component of particular brain computations or can be an explicit, conscious judgement. Psychophysical measurements of explicit relative timing have revealed clues about the interaction of sensory signals in the brain as well as in the influence of internal state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 87 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…This need not be the case, as computational studies have demonstrated large RFs could convey information about timing of stimuli (Foffani et al ., ), and SI RF expansion occurs in concert as animals learn to discriminate the timing of non‐coincident stimuli across digits (Blake et al ., ). We do not know the neural mechanisms or cortical regions serving such temporal judgments, although it has been suggested that parietal cortex is involved in comparing the timing of two stimuli (Aghdaee et al ., ). Alternatively, it is likely that the general rules of TOBT, which require the identification of a stimulus’ temporal pattern on finger locations, transfer to the temporal discrimination task and explain enhancements in temporal processing of other tactile stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…This need not be the case, as computational studies have demonstrated large RFs could convey information about timing of stimuli (Foffani et al ., ), and SI RF expansion occurs in concert as animals learn to discriminate the timing of non‐coincident stimuli across digits (Blake et al ., ). We do not know the neural mechanisms or cortical regions serving such temporal judgments, although it has been suggested that parietal cortex is involved in comparing the timing of two stimuli (Aghdaee et al ., ). Alternatively, it is likely that the general rules of TOBT, which require the identification of a stimulus’ temporal pattern on finger locations, transfer to the temporal discrimination task and explain enhancements in temporal processing of other tactile stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, repetitive transcranial magnetic stimulation has been successfully applied in diverse neuropsychiatric disorders and diseases, particularly in AD, PD and some depression symptoms [ 13 , 15 , 16 ]. High-frequency rTMS (more than 5 Hz) has been reported to deliver its signal into left dorsolateral prefrontal cortex [ 17 , 18 ]. However, low-frequency rTMS (less than 1 Hz) is able to control the activity of the right dorsolateral prefrontal cortex [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-second temporal processing of sensory information has been studied by several methodological approaches including temporal order judgment (TOJ), frequency discrimination task, time estimation tasks, and interval discrimination tasks ( 14 16 ). These various tasks differ from TDT in the neural circuits activated during the experimental procedure.…”
Section: The Temporal Discrimination Threshold (Tdt)mentioning
confidence: 99%